Influence of animal fat substitution by vegetal fat on Mortadella-type products formulated with different hydrocolloids (Scientia Agricola, 2015)
Meat has played a crucial role in human evolution and is an important component of a healthy and well-balanced diet on account of its nutritional properties, its high biological value as a source of protein, and the vitamins and minerals it supplies. We studied the effects of animal fat reduction and substitution by hydrogenated vegetal fat, sodium alginate and guar gum. Fatty acid composition, lipid oxidation, color and instrumental texture as well as the sensorial difference between low, substituted-fat and the traditional formulations for mortadella-type products were analyzed. Both substitution and reduction of animal fat decreased the saturated fatty acids percentage from 40% down to 31%. A texture profile analysis showed differences between the formulations. Furthermore, lipid oxidation values were not significant for treatments as regards the type and quantity of fat used while the use of sodium alginate and guar gum reduced the amounts of liquid released after cooking. Animal fat substitution does cause, however, a difference in overall sensorial perception compared with non-substituted products. The results confirm the viability of substituting vegetal fat for animal fat.